CdS Nanoscale Photodetectors - Deng, Kaimo; Li, Liang (Advanced materials (Weinheim), 2014)
CdS nanostructures have received much attention in recent years as building blocks for optoelectronic devices due to their unique physical and chemical properties. This progress report provides an overview of recent research about rational design of CdS nanoscale photodetectors. Three kinds of photodetectors according to the metal‐semiconductor contact types are discussed in detail: Ohmic contact, Schottky contact, and field enhanced transistor configuration. The focus is on the tuning of optical and electrical properties CdS nanostructures by element doping, composition and bandgap engineering, and heterojunction integration, along with thus modified device performances generated during these tuning processes. Latest concepts of photodetector design such as flexible, self‐powered, plasmonic, and piezophototronic photodetectors with novel properties are introduced to demonstrate the future directions of such an exciting research field. Recent advances of CdS nanoscale photodetectors with Ohmic contact, Schottky contact and MESFET configuration are summarized. Element doping, composition and bandgap engineering, heterojunction integration, and new design concepts in photodetectors are discussed. Future development directions are also discussed.